Validity and Reliability Contents of Independence Assessment Instruments of Basic Beauty Students for Class X SMK - Anggraini, Dwi; Khumaedi, Muhammad; Widowati, Trisnani (Journal of Research and Educational Research Evaluation, 2020)
This research was motivated by the absence of an instrument for assessing the independence of students in basic beauty subjects that were tested for validity and reliability. The purpose of this study was to determine the validity and reliability of the content of the students' independence assessment instruments in basic beauty subjects at SMK that had previously been compiled. The instruments developed were observation sheets for teachers and self-assessments for students. Analysis of the content validity of the instrument used the Aiken V coefficient and the reliability of the instrument content was determined by the ICC In this validity and reliability test, it involves 3 expert judgments to assess the instrument. The three expert judgments are development and research experts, beauticians, and beauty practitioners. Based on the results of this research, it shows that the observation sheet and self-assessment are proven valid with the Aiken'V coefficient of 0.69 where the score is> 0.3 and reliable with the Alpha Reliability coefficient > 0.874 and ICC = 0.698, because rxx > 0.6 thus the character assessment instrument for vocational school students can be said to be reliable. Based on the results of this research, the instrument for assessing the independence of students in basic beauty subjects at SMK in skin and hair expertise competency is suitable for use. The benefit of this research is that it can be used as a standard guide in measuring the content of students' independence instruments in learning basic beauty in SMK.